Palytoxin: an inexhaustible source of inspiration—personal perspective - Kishi, Yoshito (Tetrahedron, 2002)
A personal perspective is given on the research programs which have originated from, or are related to, the marine natural product palytoxin. The subjects discussed include: acyclic stereocontrol, Ni(II)/Cr(II)-mediated coupling reaction, stereochemical assignment via organic synthesis, universal NMR database, chiral NMR solvents, conformational analysis of C- and O-glycosides, diamond-lattice analysis, Type II O blood group determinant C- and O-trisaccharides, sMMP/ sMGP, and CH 2-bridged Watson-Crick base-pair models. A personal perspective is given on the research programs which have originated from, or are related to, the marine natural product palytoxin. The subjects discussed include: acyclic stereocontrol, Ni(II)/Cr(II)-mediated coupling reaction, stereochemical assignment via organic synthesis, universal NMR database, chiral NMR solvents, conformational analysis of C- and O-glycosides, diamond-lattice analysis, Type II O blood group determinant C- and O-trisaccharides, sMMP/ sMGP, and CH 2-bridged Watson-Crick base-pair models.